Changes in women’s lives through paid work and NGO membership: Qualitative evidence from two villages in Bangladesh - Khatun, Sufia (BRAC Institute of Governance and Development (BIGD), 2022)
Changing women’s lives through empowerment resources is important, but there are debates on how different resources of empowerment change women’s lives differently. Paid work is seen to be one of the major resources for women’s empowerment and NGO membership is one of the factors encouraging women’s self-employment. This paper is based on qualitative evidence from 25 in-depth case studies of women, conducted in two districts of Bangladesh. This paper provides evidence of the role of paid work and NGO membership in enabling women’s empowerment in their individual, family, and community life. It also examines how paid work and NGO membership together strengthens women’s self-confidence, self-worth, decision-making, financial control, mobility, and value at the individual level in the family and community. The paper tries to analyze the relative importance of paid work and NGO membership on different aspects of women’s empowerment. It also identifies some other factors influencing women’s empowerment. The paper concludes that while NGO membership, in conjunction with paid work, has a positive impact on women’s empowerment, on its own, it may not be an empowering resource in all aspects of women’s empowerment, for instance in terms of decision-making. Furthermore, norms play a role in mediating the impact of paid work and NGO membership in terms of the type of work women do, decision-making, value in the family and mobility. Additionally, other demographic characteristics, husband’s support and women’s own personality also play a role in women’s empowerment.